Pengaruh Kepemimpinan Transformasional dan Tingkat Pendidikan terhadap Perilaku Inovatif Karyawan PT MP dengan Budaya Organisasi sebagai Mediator - Natalia, Ribka; Agus Sudarya; Joko Rizkie Widokarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of transformational leadership and education level on the innovative behavior of employees at PT MP, with organizational culture as a mediating variable. The research method used a quantitative approach with a survey design on the entire employee population of 107 employees. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) through evaluation of the measurement model and structural model to assess the direct and indirect relationships between variables. The results show that transformational leadership and education level do not have a significant direct effect on employee innovative behavior. However, both have a significant influence on organizational culture. Organizational culture was shown to act as a full mediator in the relationship between transformational leadership and innovative behavior, while mediation in the relationship between education level and innovative behavior was insignificant. The conclusion of this study is that organizational culture plays a significant role in encouraging employee innovative behavior, while work experience and intrinsic motivation are aspects that need to be strengthened to increase innovation within PT MP. Keywords: Transformational Leadership, Education Level, Organizational Culture